2022
DOI: 10.3390/cells11172724
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydomonas reinhardtii Alternates Peroxisomal Contents in Response to Trophic Conditions

Abstract: Chlamydomonas reinhardtii is a model green microalga capable of heterotrophic growth on acetic acid but not fatty acids, despite containing a full complement of genes for β-oxidation. Recent reports indicate that the alga preferentially sequesters, rather than breaks down, lipid acyl chains as a means to rebuild its membranes rapidly. Here, we assemble a list of potential Chlamydomonas peroxins (PEXs) required for peroxisomal biogenesis to suggest that C. reinhardtii has a complete set of peroxisome biogenesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Peroxidase is one of the key enzymes in the enzymatic defense system of plants under adverse conditions, and acts synergistically with SOD and catalase ( CAT ) to scavenge excess free radicals in the body, thereby increasing plant resistance ( Dazy et al, 2009 ). The peroxisome gene encoded by peroxidase plays a crucial role in the cellular metabolism and pathogenicity of microalgae ( Kato et al, 2022 ). Our results showed that most peroxidase genes were down-regulated upon inhibition of NADPH oxidase-derived ROS under various stress conditions, such as peroxin-3 ( PEX3 ), peroxin-5 ( PEX5 ), peroxin-7 ( PEX7 ), peroxin-16 ( PEX16 ), and peroxin-19 ( PEX19 ) genes ( Figure 5C ).…”
Section: Resultsmentioning
confidence: 99%
“…Peroxidase is one of the key enzymes in the enzymatic defense system of plants under adverse conditions, and acts synergistically with SOD and catalase ( CAT ) to scavenge excess free radicals in the body, thereby increasing plant resistance ( Dazy et al, 2009 ). The peroxisome gene encoded by peroxidase plays a crucial role in the cellular metabolism and pathogenicity of microalgae ( Kato et al, 2022 ). Our results showed that most peroxidase genes were down-regulated upon inhibition of NADPH oxidase-derived ROS under various stress conditions, such as peroxin-3 ( PEX3 ), peroxin-5 ( PEX5 ), peroxin-7 ( PEX7 ), peroxin-16 ( PEX16 ), and peroxin-19 ( PEX19 ) genes ( Figure 5C ).…”
Section: Resultsmentioning
confidence: 99%
“…These genes encode key enzymes of acetate utilization [ 3 ] and its upregulation is a trait of mixotrophy [ 8 ]. Acetyl groups provide algae cells with energy through the TCA cycle or due to the glyoxylate cycle [ 2 , 39 ]. CIS1 also exhibited a higher expression in the MM variant in comparison with MA at the beginning of Chlamydomonas growth.…”
Section: Discussionmentioning
confidence: 99%